المحتوى الثقافي في "كتاب العربية بين يديك" : دراسة تقويمية /‏ - عيسى، محمود عبد الفتاح إبراهيم
This study aims to evaluate the cultural content of the book "Al-Arabiya Bayna Yadyaka” through the development of common standards between Rushdi Ahmed To'eima's standards, the standards of the American Council of Teachers of Foreign Languages, and the standards of the common European framework; the mentioned standards have achieved widespread use and exchange among interested parties and experts, both in the teaching of foreign languages or in the teaching of Arabic to non-native speakers. From this perspective, the researcher starts by defining culture, its essence, its determinants and its standards. He then exposes and discusses the three abovementioned criteria, to later present the reasons behind selecting each of them and pursues that by offering an explanatory introduction to the book "Al-Arabiya Bayna Yadyaka "; after which the currency and reality of the book's cultural content are also explained. Finally, the researcher establishes an instrument to evaluate the cultural content of the book from the three criteria. In the evaluation process, Excel was chosen as the instrument. It is hoped that this study will be a new nucleus for the development of modern tools and innovation in evaluating books that teach Arabic to non-native speakers, and avoid patterning in evaluation; this would raise the level of the preparation of Arabic teaching books to non-native speakers. This would also be positively reflected in turn on the level of Arabic learners who are non-native. The study reached significant results, including: the importance of the mixed selected Arab, American and European standards in the assessment of the cultural content of the book; the book has proved that its cultural content is compatible with most international standards for evaluation, and the book needs to be complemented with some additions and amendments in its cultural content in order to address its shortcomings.